Accounting Information System of Sales and Cash Receivings for Internal Control in Pt. Human Power - Herni Pujiati; Yusnaldi (Jurnal Mantik, 2022)
This study aims to determine how the information system in accounting sales and cash receipts on internal control at PT. Human Power. The type of research is a qualitative descriptive method. Data collection techniques were carried out using observation, interviews, and documentation. The results showed that the sales accounting information system and cash receipts were applied to PT. Human Power has used a computerized system quite well although there are still shortcomings, namely the existence of several different functions that are carried out by one person so it is not right with the existing theory. In addition, the procedure for depositing cash into the bank should not only be done once a week. Companies should add employees to the functions that concurrently work. This method is a form of company internal control to prevent the occurrence of fraud and error. The procedure for depositing cash into the bank should also be carried out every day, exactly one day after the cash is received.